Implementasi model pembelajaran team assisted individualization (TAI) untuk meningkatkan keterampilan pemecahan masalah perkalian bilangan cacah peserta didik kelas V sekolah dasar - Dewi Istikomah Hidayatullah; Riyadi Riyadi; Idam Ragil Widianto Atmojo (Didaktika Dwija Indria, 2020)
The purpose of this research is to improve problem solving skills multiplication whole numbers by Team Assisted individualization (TAI) learning model. This research is Classroom Action Research two cycles with 4 meetings. The subjects research were students of III clas at SDN Karangasem I Surakarta in the 2019/2020 academic years. This research uses observation, interviews, tests and documentation to collected the data. The validity of the data uses source triangulation and technique triangulation. The analysis of the data used Miles and Huberman model. Result of research on pre-action shows conditions of problem solving skills 3,23% classically. The first cycle increase to 54,84% in classical. The research continued with the second cycle, increase to 93,55% in classical. Based on the result of research TAI learning model can improve problem solving skills multiplication whole number students of III class at SDN Karangasem I Surakarta in the 2019/2020 academic years.